(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
English occupies an important place in the world today. It seems obvious that it is impossible to teach all the knowledge, skills, methods, techniques, which are of potential use to teachers. It seems advisable to teach the teachers and caregivers in such a way as to strengthen their dispositions go on learning, to be resourceful and to be inventive. Teaching language is hard work. Learning the rules of punctuation and structure can be less appealing to kids than the more obviously creative and fun aspects of writing.